Practice and clinical decision-making autonomy among Hellenic critical care nurses - Papathanassoglou, Elizabeth; Tseroni, Maria; Karydaki, Athena (My University, 2005)
Background: Nursing autonomy has been associated with better patient-outcomes; therefore, it is a priority for critical care nursing management. Low authority has been a persistent complaint of Hellenic intensive care unit nurses; however, issues of nursing autonomy have not been previously addressed empirically in Hellas. Purpose: To investigate: (1) the perceived contribution to clinical decision-making, (2) the degree of autonomy in technical tasks, and (3) factors related to practice autonomy in critical care nurses in Hellas. Additionally, because of the lack of sufficient tools, this study also aimed to construct and to validate a new tool for assessing practice and clinical decision-making autonomy among Hellenic intensive care unit nurses. Materials and methods: A Hellenic intensive care nursing autonomy scale, focused on technical aspects of care, was developed through literature review, a panel of experts and a pilot study in a random sample of 120 respondents. Items were refined by factor analysis, which revealed three major conceptual categories of autonomy: (1) basic technical, (2) advanced technical, and (3) clinical decision. Hellenic intensive care nursing autonomy (Likert 4, range: 38-152), was distributed to all nurses employed in intensive care units in Hellas (n = 807; attrition: 27%). Comparisons, correlation and multivariate regression were employed. Results: The Hellenic intensive care nursing autonomy scale exhibited appropriate reliability (Cronbach's α = 0.86) and validity properties. Autonomy scores were moderate (mean: 105.24 ± 9.58). Highest autonomy was attributed to basic technical tasks, followed by advanced technical tasks and decision-making. Male gender and higher education were predictors of higher overall, advanced technical and decision-making autonomy (P = 0.01). Bachelor degree graduates scored higher in decisional autonomy (P = 0.03). Intensive care unit experience and type of intensive care unit were also important determinants of decisional autonomy (P = 0.02). Conclusions: The results revealed moderate autonomy in technical tasks and low decisional autonomy among Hellenic intensive care unit nurses. Factors related to the educational preparation of nurses, gender issues and institutional characteristics might hinder intensive care unit nurses' autonomy in Hellas
Keywords: Nursing--Management; Nurses; Greece; Intensive care units